If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 3xy + -1y = 0 Solving 4x + 3xy + -1y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'y' to each side of the equation. 4x + 3xy + -1y + y = 0 + y Combine like terms: -1y + y = 0 4x + 3xy + 0 = 0 + y 4x + 3xy = 0 + y Remove the zero: 4x + 3xy = y Combine like terms: y + -1y = 0 4x + 3xy + -1y = 0 The solution to this equation could not be determined.
| 2(1-x)+6x=2(x+1) | | 4/5-8x=-1/5 | | x=2pi^2 | | 12=6[-3-x] | | x=1/2*75*100 | | 2/5x=3/8 | | 1/2*75*100 | | 3/5y-3=8-1/5y | | 2(x-3)=5(x+2) | | f-3/6=1/6 | | 6v^2-24v-72=0 | | x=1/2*175*90 | | 11=5+s | | 10+2w=16 | | 5x+50=-10 | | 214/300 | | 16n+3+2n=15n+5 | | x=1/2*100*75 | | 3-6x*3=7x-1 | | 450000q-150000q-3200000=0 | | -4[2r+-5]=-44 | | [3x-7]=5 | | x=1/2*20*35 | | 9+y=119 | | 10b+6bn+4=36 | | 6r-21+6r-15= | | a*b*c=4 | | -4b-7(b+6)=-130 | | 2r+2=-14 | | 9k=7 | | 2x^2=7-5x | | -15=-3+-2k |